A responsabilidade tributária e os grupos econômicos - Oleinik, Rosana (2016)
In the current world economic organization, an increasing number of the concentration of companies in conglomerates, in order to maximize profit and solidify its market performance. The Brazilian tax authorities, aware of this fact, created thesis, which want to apply joint and several liability provided for in art. 124, I, of the National Tax Code, companies that make up these clusters, under the allegation of common interest. Indeed, another advantage envisioned by the Treasury would be the interruption of prescription for the redirection of tax foreclosures arranged in art. 125, the National Tax Code, if solidarity is recognized. This strategy would prevent a wide range of tax foreclosures often filed outside the limitation lapse succumbed, compared to the demonstrated inertia. Our goal with this study was to examine whether, before the provisions of constitutional tax system and the tax code, the tax authorities of the reasons could thrive. To this end, we fix a definition of "economic group" that would serve the Tax Law, regarding the joint liability and concluded that not enough single command, being a necessary condition to the common interest in making the fact enforceable. We analyze the existing reporting relationships in tax law, the need for complementary law providing for passive subjection and their respective treatment in the tax code. We are also concerned to launch our attention to procedural and procedural aspects present in the National Tax Code and the Tax Enforcement Law and Article 50 of the Civil Code, to understand how the tax could be made in the face of the companies composing the business groups. Given this effort, we concluded only be possible to the constitution of the tax credit in the face of business partnerships that comprise economic group, in case of joint realization of even enforceable fact, at the time of occurrence of the tax liability. The recovery of the claim, formed after the certificate of outstanding debt, the redirection will be held due to fraudulent behavior, which involves third parties, or, in responsibility for or violations